Nanosheet wrapping-assisted coverslip-free imaging for looking deeper into a tissue at high resolution. - Hong Zhang; Kenji Yarinome; Ryosuke Kawakami; Kohei Otomo; Tomomi Nemoto; Yosuke Okamura (PLoS ONE, 2020)
In order to achieve deep tissue imaging, a number of optical clearing agents have been developed. However, in a conventional microscopy setup, an objective lens can only be moved until it is in contact with a coverslip, which restricts the maximum focusing depth into a cleared tissue specimen. Until now, it is still a fact that the working distance of a high magnification objective lens with a high numerical aperture is always about 100 μm. In this study, a polymer thin film (also called as nanosheet) composed of fluoropolymer with a thickness of 130 nm, less than one-thousandth that of a 170 μm thick coverslip, is employed to replace the coverslip. Owing to its excellent characteristics, such as high optical transparency, mechanical robustness, chemical resistance, and water retention ability, nanosheet is uniquely capable of providing a coverslip-free imaging. By wrapping the tissue specimen with a nanosheet, an extra distance of 170 μm for the movement of objective lens is obtained. Results show an equivalently high resolution imaging can be obtained if a homogenous refractive index between immersion liquid and mounting media is adjusted. This method will facilitate a variety of imaging tasks with off-the-shelf high magnification objectives.